Carbon-silicon nanofiber negative electrode material and preparation method thereof

By using carbon-silicon nanofiber negative electrode material in lithium-ion batteries, the high-porosity carbon fiber structure is used to improve conductivity and stability, the problem of silicon-based materials poor volume expansion and conductivity in lithium-ion batteries is solved, and a higher level of performance has been achieved. Cycling performance and first charge efficiency.

CN119275258AActive Publication Date: 2025-01-07HEFEI GUOXUAN HIGH TECH POWER ENERGY

Patent Information

Application Number
CN202411195786.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-07
Estimated Expiration
2044-08-29

AI Technical Summary

Technical Problem

The silicon-based materials in lithium-ion batteries have significant volume expansion and poor conductivity during charging and discharging, resulting in short service life and low initial charging efficiency. Existing improvement measures such as nano-treatment and carbon coating have not effectively improved cycling performance.

Method used

Using carbon-silica nanofiber negative electrode material, by mixing water-soluble lignin sulfonate with polyvinyl alcohol, adding porous silicon micropowder, electrospinning and high-temperature carbonization, a high porosity carbon fiber structure is formed, which improves conductivity and avoids silicon. Aggregate and expand.

Benefits of technology

It significantly improves the first round of Coulomb efficiency and cycling performance of lithium-ion batteries, alleviates the volume expansion problem of micron-scale silicon materials, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275258A_ABST
    Figure CN119275258A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon-silicon nanofiber negative electrode material and a preparation method thereof.The preparation method comprises the steps that lignosulfonate powder and polyvinyl alcohol powder are mixed, dissolved and stirred, and a lignosulfonate-polyvinyl alcohol solution is obtained; the preparation method comprises the following steps: adding porous silica powder into a lignosulfonate-polyvinyl alcohol solution and uniformly dispersing, so that the porous silica powder is uniformly dispersed in lignosulfonate-polyvinyl alcohol to form a unique structure, and then carrying out electrostatic spinning and carbonization to obtain the high-porosity composite material. According to the carbon-silicon nanofiber negative electrode material, the first-round coulombic efficiency of the battery can be effectively improved, the problem of volume expansion of a micron-sized silicon material is relieved, and the lithium ion battery assembled by the carbon-silicon nanofiber negative electrode material has relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a carbon-silicon nanofiber negative electrode material and a preparation method thereof. Background Art

[0002] In the field of new energy, lithium-ion batteries have become the focus of global research due to their high specific energy, long service life and portability, and are widely used in a variety of electronic devices, electric vehicles and portable storage devices. As an emerging negative electrode material for lithium-ion batteries, silicon has a theoretical specific capacity of up to 4000mAh / g, but its volume expands significantly during the charging and discharging process, and it is easy to pulverize and fall off. The conductivity of micron-level silicon materials is poor, and these problems seriously limit its service life. Especially during the initial charge, lithium ions react with silicon oxide to form compounds, consuming a large amount of active lithium and resulting in low initial charging efficiency.

[0003] In order to improve the conductivity of silicon-based materials and control their volume expansion, industry experts have adopted a variety of strategies, such as nano-processing, carbon coating and composite with graphite. These technologies can improve the conductivity of the material to a certain extent, while avoiding direct contact between the electrolyte and silicon, which is conducive to stabilizing the solid electrolyte interface (SEI) film. However, these improvements still face many challenges, including limited improvement in cycle performance and low initial charging efficiency. The typical cycle life is only about 500 times. Therefore, the development of a carbon-silicon negative electrode material that can effectively reduce volume expansion, ensure battery cycle stability, and have high initial charging efficiency and excellent cycle performance is still an urgent technical challenge facing the lithium-ion battery field. Summary of the invention

[0004] Based on the technical problems existing in the background technology, the present invention proposes a carbon-silicon nanofiber negative electrode material and a preparation method thereof, which can effectively improve the first-round coulomb efficiency of the battery and alleviate the problem of volume expansion of micron-sized silicon materials. The lithium-ion battery assembled therefrom has better cycle performance.

[0005] The present invention provides a method for preparing a carbon-silicon nanofiber negative electrode material, comprising the following steps:

[0006] S1, mixing water-soluble lignin sulfonate powder and polyvinyl alcohol powder, and adding them into deionized water to completely dissolve them to obtain a lignin sulfonate-polyvinyl alcohol solution;

[0007] S2, adding porous silicon powder to the lignin sulfonate-polyvinyl alcohol solution and dispersing the powder evenly to obtain a precursor solution;

[0008] S3, electrospinning the precursor solution to obtain lignin sulfonate-silicon nanofibers;

[0009] S4, heating the lignin sulfonate-silicon nanofibers for pre-carbonization, and then carbonizing them at high temperature under an inert atmosphere to obtain a carbon-silicon nanofiber negative electrode material.

[0010] In the present invention, the addition of lignin sulfonate increases the structural porosity of the outer carbon layer material of porous silicon, improves the conductivity of the material, and forms an excellent internal conductive network; the porous silicon is dispersed in the high-porosity carbon fiber structure formed by carbonization, which effectively avoids the aggregation and expansion of silicon during the battery charging and discharging process; this structural design significantly improves the cycle performance of the material, can effectively improve the first-round coulomb efficiency of the battery, and alleviate the problem of volume expansion of micron-level silicon materials, and the lithium-ion battery assembled therefrom has better cycle performance.

[0011] In S1, the dissolving method may be, for example, heating and stirring. The heating and stirring temperature is preferably 25 to 90°C, for example, 25°C, 35°C, 45°C, 55°C, 65°C, 75°C, or 90°C.

[0012] In S1, after the dissolution is complete, a cooling step may be further included, and the cooling time is preferably 24 to 36 hours, for example, 24 hours, 30 hours, or 36 hours.

[0013] Preferably, the mass ratio of the water-soluble lignin sulfonate powder to the polyvinyl alcohol powder is 0.8 to 1.2: 1. In the present invention, by controlling the ratio of lignin sulfonate to polyvinyl alcohol, it is possible to ensure that the fibers obtained by electrospinning have excellent formability and uniformity, which is beneficial to further improve the structural stability and conductivity of the final carbon silicon nanofiber negative electrode material.

[0014] Preferably, the total mass ratio of the water-soluble lignin sulfonate powder and the polyvinyl alcohol powder to the porous silicon powder is 8:1 to 3, for example, 8:1, 8:2, 8:3. In the present invention, by controlling the content of porous silicon powder in the precursor, the carbon silicon nanofiber negative electrode material can have both high specific capacity and good volume expansion rate, thereby having excellent comprehensive performance.

[0015] Preferably, in S1, the ratio of the water-soluble lignin sulfonate powder to deionized water is 2 g: 10-20 mL.

[0016] Preferably, in S2, the dispersing step comprises: stirring for 1 to 4 hours, and then ultrasonically dispersing for 1 to 4 hours; for example, stirring for 1 hour, 2 hours, 3 hours, and 4 hours; and ultrasonically dispersing for 1 hour, 2 hours, 3 hours, and 4 hours.

[0017] Preferably, the specific surface area of ​​the porous silicon powder is 50 to 320 m 2 / g, and the pore size is 2-15nm. In the present invention, by controlling the specific surface area and pore size of porous silicon powder, the specific capacity of the material can be further improved, the volume expansion can be buffered, and the material can have better electrochemical performance.

[0018] Preferably, the preparation method of the porous silicon powder comprises: adding silicon aluminum alloy to an acid solution, stirring and reacting at room temperature to obtain; preferably, the concentration of the acid solution is 0.2mol / L to 0.8mol / L; preferably, the acid solution is one or a mixture of hydrochloric acid solution, sulfuric acid solution, and carbonic acid solution; preferably, the stirring reaction time is 6 to 18 hours. After the stirring reaction, conventional post-processing steps may also be included, including: solid-liquid separation, washing, and drying; the drying method may be, for example, vacuum drying or freeze drying.

[0019] Preferably, the porous silicon micropowder is porous silicon micropowder coated with polydiallyldimethylammonium chloride.

[0020] Preferably, the method for preparing the porous silicon micropowder coated with polydiallyldimethylammonium chloride comprises:

[0021] Adding silicon aluminum alloy to an acid solution, stirring and reacting at room temperature to obtain porous silicon powder; preferably, the concentration of the acid solution is 0.2 mol / L to 0.8 mol / L; preferably, the acid solution is one or a mixture of hydrochloric acid solution, sulfuric acid solution, and carbonic acid solution; preferably, the stirring reaction time is 6 to 18 hours; after the stirring reaction, conventional post-processing steps may also be included, including: solid-liquid separation, washing, and drying; the solid-liquid separation method may be, for example, centrifugation or filtration, and the drying method may be, for example, vacuum drying or freeze drying;

[0022] Dispersing the porous silicon micropowder in water to obtain an aqueous dispersion of the porous silicon micropowder; preferably, the aqueous dispersion of the porous silicon micropowder has a solid content of 1 to 3%;

[0023] Add polydiallyldimethylammonium chloride to an aqueous dispersion of porous silicon micropowder, and stir the reaction at room temperature to obtain porous silicon micropowder coated with polydiallyldimethylammonium chloride; preferably, the mass of the polydiallyldimethylammonium chloride is equivalent to 10% to 20% of the mass of the porous silicon micropowder; preferably, the stirring reaction time is 1 to 4 hours; after the stirring reaction, conventional post-processing steps may also be included, including: solid-liquid separation, washing, and drying; the solid-liquid separation method may be, for example, centrifugation or filtration, and the drying method may be, for example, vacuum drying or freeze drying.

[0024] In the present invention, porous silicon micropowder is further coated by polydiallyldimethylammonium chloride, which can be more tightly combined with sodium lignin sulfonate through electrostatic action, and a carbon layer can be formed on the surface of porous silicon after carbonization, thereby improving the bonding stability between porous silicon and high-porosity carbon fiber, and further improving the structural stability of the formed carbon-silicon nanofiber negative electrode material, thereby improving the cycle performance and conductivity of the material.

[0025] Preferably, in S3, the electrospinning conditions include: voltage of 20 kV, flow rate of 0.6-1 mL / h, and collection distance of 14-16 cm. In the present invention, by controlling reasonable electrospinning parameters, it is beneficial to obtain more uniform fibers, thereby further improving the structural stability of the final carbon silicon nanofiber negative electrode material.

[0026] Preferably, in S4, the pre-carbonization temperature is 200-300°C; for example, it can be 200°C, 250°C, or 300°C.

[0027] Preferably, in S4, the pre-carbonization time is 4 to 6 hours; for example, it can be 4 hours, 5 hours, or 6 hours.

[0028] Preferably, in S4, the temperature of the high temperature carbonization is 700-900°C; for example, it may be 700°C, 750°C, 800°C, 850°C, or 900°C.

[0029] Preferably, in S4, the high temperature carbonization time is 1 to 3 hours; for example, it can be 1 hour, 2 hours, or 3 hours.

[0030] In the present invention, by controlling the temperature and time of pre-carbonization and high-temperature carbonization of the precursor fibers, the fibers can be more fully carbonized, thereby further improving the structural stability and conductivity of the carbon silicon nanofiber negative electrode material.

[0031] In S4, after high-temperature carbonization, conventional post-processing steps such as cooling and grinding may also be included.

[0032] In the present invention, the inert atmosphere refers to a non-reactive atmosphere, that is, an atmosphere formed by one or more of nitrogen or an inert gas such as argon and helium.

[0033] The invention also provides a carbon silicon nanofiber negative electrode material, which is prepared by the preparation method.

[0034] The present invention also proposes the use of the carbon silicon nanofiber negative electrode material as a negative electrode material for a lithium ion battery.

[0035] The beneficial effects of the present invention are as follows:

[0036] The invention discloses a carbon silicon nanofiber negative electrode material and a preparation method thereof, wherein lignin sulfonate powder and polyvinyl alcohol powder are ground, dissolved and stirred to obtain a lignin sulfonate-polyvinyl alcohol solution; porous silicon micropowder is added to the lignin sulfonate-polyvinyl alcohol solution and dispersed evenly, so that the porous silicon micropowder is evenly dispersed in the lignin sulfonate-polyvinyl alcohol to form a unique structure, and then a high-porosity composite material is obtained after electrostatic spinning and carbonization. The carbon silicon nanofiber negative electrode material of the invention can effectively improve the first-round coulomb efficiency of the battery, alleviate the problem of volume expansion of micron-level silicon materials, and the lithium ion battery assembled therefrom has better cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 It is a schematic diagram of the preparation process flow of the carbon-silicon nanofiber negative electrode material proposed in the present invention and a schematic diagram of the structure of the prepared carbon-silicon nanofiber negative electrode material.

[0038] Figure 2 This is the XRD pattern of the carbon silicon nanofiber negative electrode material prepared in Example 1.

[0039] Figure 3 This is the Raman spectrum of the carbon silicon nanofiber negative electrode material prepared in Example 1.

[0040] Figure 4 This is a cycle performance diagram of the carbon silicon nanofiber negative electrode material prepared in Example 1.

[0041] Figure 5 This is the first cycle charge and discharge curve of the carbon silicon nanofiber negative electrode material prepared in Example 1. DETAILED DESCRIPTION

[0042] The technical solution of the present invention is described in detail below through specific embodiments.

[0043] Example 1

[0044] A method for preparing a carbon-silicon nanofiber negative electrode material comprises the following steps:

[0045] S1. Mix 2 g of sodium lignin sulfonate powder and 2 g of polyvinyl alcohol powder and grind them evenly, then add them into 15 mL of deionized water and heat and stir at 50 ° C until they are completely dissolved, and then cool for 18 hours to obtain a lignin sulfonate-polyvinyl alcohol solution;

[0046] S2. Add 10g of silicon-aluminum alloy into 500mL of 0.5mol / L hydrochloric acid solution, stir and react at room temperature for 9h, then vacuum filter, wash with deionized water, and vacuum dry to obtain porous silicon powder with a specific surface area of ​​132m 2 / g, pore size is 2-15nm;

[0047] 1.5 g of the porous silicon powder obtained above was added to the lignin sulfonate-polyvinyl alcohol solution obtained in S1, stirred for 2 h, and then ultrasonically dispersed for 2 h to obtain a precursor solution;

[0048] S3, transferring the precursor solution obtained in S2 into a 20 mL syringe, and performing electrospinning to obtain lignin sulfonate-silicon nanofibers, the electrospinning voltage is 20 kV, the flow rate is 0.8 mL / h, and the collection distance between the syringe needle and the collector is 15 cm;

[0049] S4. The lignin sulfonate-silicon nanofibers obtained in S3 are first kept at 260°C for 5 hours, then carbonized at 800°C in a nitrogen atmosphere, cooled to room temperature, and then ground evenly to obtain a carbon-silicon nanofiber negative electrode material.

[0050] The carbon silicon nanofiber negative electrode material obtained in Example 1 was characterized. Figure 2 This is the XRD pattern of the carbon silicon nanofiber negative electrode material prepared in Example 1. Figure 3 This is the Raman spectrum of the carbon silicon nanofiber negative electrode material prepared in Example 1. Figure 2 , Figure 3 It can be seen that no other impurity phases are detected in the composite material; the Raman map shows the presence of amorphous carbon, which introduces surface vacancies and lattice defects into the material. Due to the presence of these defects, the electrochemical reaction surface area of ​​the material can be increased, providing more active sites for the reaction, promoting charge transfer and material diffusion. In addition, defects can also adjust the lattice structure and electronic structure of the material, change its band structure and electron affinity and other characteristics, thereby further improving its electrochemical performance.

[0051] The electrochemical performance of the carbon silicon nanofiber negative electrode material obtained in Example 1 was tested. Figure 4 This is a cycle performance diagram of the carbon silicon nanofiber negative electrode material prepared in Example 1. Figure 5 This is the first cycle charge and discharge curve of the carbon silicon nanofiber negative electrode material prepared in Example 1. Figure 4 , Figure 5 It can be seen that the prepared material has a high initial discharge specific capacity of 1384.6 mAh / g. After 100 cycles of charge and discharge at a current density of 0.2C, it can still maintain a high capacity with a capacity retention rate of 98.5%.

[0052] Example 2

[0053] A method for preparing a carbon-silicon nanofiber negative electrode material comprises the following steps:

[0054] S1. Mix 2 g of sodium lignin sulfonate powder and 2 g of polyvinyl alcohol powder and grind them evenly, then add them into 15 mL of deionized water and heat and stir at 50 ° C until they are completely dissolved, and then cool for 18 hours to obtain a lignin sulfonate-polyvinyl alcohol solution;

[0055] S2. Add 10g of silicon-aluminum alloy into 500mL of 0.8mol / L hydrochloric acid solution, stir and react at room temperature for 6h, then vacuum filter, wash with deionized water, and vacuum dry to obtain porous silicon powder with a specific surface area of ​​184m 2 / g, pore size is 2-15nm;

[0056] 1 g of the porous silicon powder obtained above was added to the lignin sulfonate-polyvinyl alcohol solution obtained in S1, stirred for 2 h, and then ultrasonically dispersed for 2 h to obtain a precursor solution;

[0057] S3, transferring the precursor solution obtained in S2 into a 20 mL syringe, and performing electrospinning to obtain lignin sulfonate-silicon nanofibers, the electrospinning voltage is 20 kV, the flow rate is 0.6 mL / h, and the collection distance between the syringe needle and the collector is 15 cm;

[0058] S4. The lignin sulfonate-silicon nanofibers obtained in S3 are first kept at 200°C for 6 hours, then carbonized at 700°C in a nitrogen atmosphere, cooled to room temperature, and then ground evenly to obtain a carbon-silicon nanofiber negative electrode material.

[0059] Example 3

[0060] A method for preparing a carbon-silicon nanofiber negative electrode material comprises the following steps:

[0061] S1. Mix 2 g of sodium lignin sulfonate powder and 2 g of polyvinyl alcohol powder and grind them evenly, then add them into 15 mL of deionized water and heat and stir at 50 ° C until they are completely dissolved, and then cool for 18 hours to obtain a lignin sulfonate-polyvinyl alcohol solution;

[0062] S2. Add 10g of silicon aluminum alloy into 500mL of 0.2mol / L hydrochloric acid solution, stir and react at room temperature for 18h, then vacuum filter, wash with deionized water, and vacuum dry to obtain porous silicon powder with a specific surface area of ​​220m 2 / g, pore size is 2-15nm;

[0063] 0.5 g of the porous silicon powder obtained above was added to the lignin sulfonate-polyvinyl alcohol solution obtained in S1, stirred for 2 h, and then ultrasonically dispersed for 2 h to obtain a precursor solution;

[0064] S3, transferring the precursor solution obtained in S2 into a 20 mL syringe, and performing electrospinning to obtain lignin sulfonate-silicon nanofibers, the electrospinning voltage is 20 kV, the flow rate is 1 mL / h, and the collection distance between the syringe needle and the collector is 15 cm;

[0065] S4. The lignin sulfonate-silicon nanofibers obtained in S3 are first kept at 300°C for 4 hours, then carbonized at 900°C in a nitrogen atmosphere, cooled to room temperature, and then ground evenly to obtain a carbon-silicon nanofiber negative electrode material.

[0066] Example 4

[0067] The only difference between Example 4 and Example 1 is that porous silicon micropowder coated with polydiallyldimethylammonium chloride is used instead of porous silicon micropowder;

[0068] The specific preparation method of porous silicon micropowder coated with polydiallyldimethylammonium chloride is as follows:

[0069] 10 g of silicon-aluminum alloy was added to 500 mL of 0.8 mol / L hydrochloric acid solution, stirred at room temperature for 6 h, and then vacuum filtered, washed with deionized water, and vacuum dried to obtain porous silicon powder;

[0070] Dispersing porous silicon micropowder in water to obtain a porous silicon micropowder aqueous dispersion having a solid content of 2%;

[0071] Polydiallyldimethylammonium chloride equivalent to 10% of the mass of porous silicon micropowder is added to the aqueous dispersion of porous silicon micropowder, stirred and reacted at room temperature for 2 hours, and then vacuum filtered, washed with deionized water, and vacuum dried to obtain porous silicon micropowder coated with polydiallyldimethylammonium chloride.

[0072] Comparative Example 1

[0073] A method for preparing a carbon-silicon nanofiber negative electrode material comprises the following steps:

[0074] S1. Add 4 g of polyvinyl alcohol powder into 15 mL of deionized water, heat and stir at 50° C. until completely dissolved, and then cool for 18 h to obtain a polyvinyl alcohol solution;

[0075] S2. Add 10g of silicon-aluminum alloy into 500mL of 0.5mol / L hydrochloric acid solution, stir and react at room temperature for 9h, then vacuum filter, wash with deionized water, and vacuum dry to obtain porous silicon powder with a specific surface area of ​​132m 2 / g, pore size is 2-15nm;

[0076] 1.5 g of the porous silicon powder obtained above was added to the polyvinyl alcohol solution obtained in S1, stirred for 2 h, and then ultrasonically dispersed for 2 h to obtain a precursor solution;

[0077] S3, transferring the precursor solution obtained in S2 into a 20 mL syringe, and performing electrospinning to obtain silicon-containing nanofibers, the electrospinning voltage is 20 kV, the flow rate is 0.8 mL / h, and the collection distance between the syringe needle and the collector is 15 cm;

[0078] S4. The silicon-containing nanofibers obtained in S3 are first kept at 260° C. for 5 h, then carbonized at 800° C. in a nitrogen atmosphere, cooled to room temperature, and then ground evenly to obtain a carbon-silicon nanofiber negative electrode material.

[0079] A lithium ion battery was prepared using the negative electrode materials prepared in Examples 1 to 4 and Comparative Example 1, and its electrochemical performance was tested. The test results are shown in Table 1:

[0080] Table 1

[0081]

[0082]

[0083] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a carbon-silicon nanofiber negative electrode material, characterized in that: The following steps are involved: S1, mixing water-soluble lignin sulfonate powder and polyvinyl alcohol powder, and adding them into deionized water to completely dissolve them to obtain a lignin sulfonate-polyvinyl alcohol solution; S2, adding porous silicon powder to the lignin sulfonate-polyvinyl alcohol solution and dispersing the powder evenly to obtain a precursor solution; S3, electrospinning the precursor solution to obtain lignin sulfonate-silicon nanofibers; S4, heating the lignin sulfonate-silicon nanofibers for pre-carbonization, and then carbonizing them at high temperature under an inert atmosphere to obtain a carbon-silicon nanofiber negative electrode material.

2. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: The mass ratio of the water-soluble lignin sulfonate powder to the polyvinyl alcohol powder is 0.8-1.2:

1.

3. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: The mass ratio of the total mass of the water-soluble lignin sulfonate powder and the polyvinyl alcohol powder to the mass of the porous silicon powder is 8:1-3.

4. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: The specific surface area of ​​the porous silicon powder is 50 to 320 m 2 / g, pore size is 2~15nm.

5. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: The porous silicon micropowder is porous silicon micropowder coated with polydiallyldimethylammonium chloride.

6. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: In S3, the electrospinning conditions include: a voltage of 20 kV, a flow rate of 0.6 to 1 mL / h, and a collection distance of 14 to 16 cm.

7. The method for preparing the carbon-silicon nanofiber negative electrode material according to claim 1, characterized in that: In S4, the temperature of the pre-carbonization is 200-300°C, and the time is 4-6 hours; in S4, the temperature of the high-temperature carbonization is 700-900°C, and the time is 1-3 hours.

8. A carbon silicon nanofiber negative electrode material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Silicon@carbon-graphene-based flexible composite material and preparation method thereof and lithium battery

    CN108807842A

  • Battery anode plate, preparation method thereof, and lithium ion battery

    CN109301248A

  • Si / C composite fiber material as well as preparation method and application thereof

    CN113493943A

  • Spinning solution and preparation method thereof

    CN113493944A

  • Porous silicon / carbon composite negative electrode material of lithium ion battery, preparation method of porous silicon / carbon composite negative electrode material and lithium ion battery

    CN114695887A

Cited By

  • Preparation method of nitrogen-doped carbon-silicon nanofiber and application of nitrogen-doped carbon-silicon nanofiber in lithium ion battery negative electrode material

    CN122257241A